Effects of German and Maize Grasses on Milk and Blood Of Dairy Cows (Research in Agriculture Livestock and Fisheries, 2023)
The objectives of this study were to determine carbohydrates such as glucose, total protein, lipid parameters, mineral levels in blood; qualitative characteristics such as fat, SNF, lactose, total solids and protein percentages of milk; and the quantity of milk after feeding german and maize fodders. Thirty clinically and apparently healthy cows were selected and divided into three homogenous groups. Control group was fed mixed grass, another group was fed german grass and the last one was fed maize grass. Milk and blood samples were collected from the cows (n-30) before the study commenced. Again milk and blood samples were collected on day 30 and day 60. After collection, milk samples were analyzed by Milk Analyzer MIA-SLP-60 for proximate components. Serum samples were analyzed by different colorimetric techniques using a spectrophotometer (Humalyzer 3000®) and kits from Randox (Ireland). In addition, daily milk production records of cows were maintained. The study found a significant rise of SNF and solids, a highly significant increase of lactose and protein in the maize feed group (M), and a highly significant positive change of fat percentage in the german fed (G) group. The average daily milk production of the M and G group were respectively 11.39% and 6.98% higher than the control group. No significant change was found in hematological and biochemical parameters of blood. Further intensive long term investigation to establish relation between blood parameters and milk yield and milk quality should be carried out.Vol. 9, No. 3, December 2022: 313-322